Los anublos comun y fusco - Yoshii, K. (International Center for Tropical Agriculture, 1980)
Common blight (Xanthomonas phaseoli) and fuscous bright (Xanthomonas phaseoli var. fuscans) are the major bacterial diseases of beans. The 2 organisms are found frequently in association and are present in numerous bean production regions of the world. High temp and RH are favorable conditions for the development of the disease. The infection by the bacteria produces water spots on the leaves, stems, pods and seeds. The disease can be controlled by cultural practices such as the use of disease-free seed, proper crop rotation and deep plowing; various chemical products have been used in seed treatment or as a foliage protectant before the infection becomes severe; and by the utilization of resistant var. The symptoms and damage caused by the diseases are illustrated in color. (CIAT)